2020
DOI: 10.1080/19401493.2020.1838612
|View full text |Cite
|
Sign up to set email alerts
|

Fluid temperature predictions of geothermal borefields using load estimations via state observers

Abstract: Fluid temperature predictions of geothermal borefields usually involve temporal superposition of its characteristic g-function, using load aggregation schemes to reduce computational times. Assuming that the ground has linear properties, it can be modeled as a linear state space system where the states are the aggregated loads. However, the application and accuracy of these models is compromised when the borefield is already operating and its load history is not registered or there are gaps in the data. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore a larger minimum number of short-term states or a larger short-term radius r ST should be enforced. The error obtained with the analytical formulation from Cupeiro Figueroa et al ( , 2021 is always minimal, in the order of 10 −2 K. However, the number of states of the analytical model for 25 years rises to 96 states in both cases, while the proposed RC models have only 15 states in the 4 boreholes field and 12 in the 37 boreholes field. An increase of the error at the end of the considered 25 years period is observed for both controller models.…”
Section: Model Validation and Comparisonmentioning
confidence: 89%
See 3 more Smart Citations
“…Therefore a larger minimum number of short-term states or a larger short-term radius r ST should be enforced. The error obtained with the analytical formulation from Cupeiro Figueroa et al ( , 2021 is always minimal, in the order of 10 −2 K. However, the number of states of the analytical model for 25 years rises to 96 states in both cases, while the proposed RC models have only 15 states in the 4 boreholes field and 12 in the 37 boreholes field. An increase of the error at the end of the considered 25 years period is observed for both controller models.…”
Section: Model Validation and Comparisonmentioning
confidence: 89%
“…The deviations between the proposed RC model vs the IBPSA borefield model and the analytical controller model of Cupeiro Figueroa et al ( , 2021 vs the IBPSA borefield model are shown in Figure 5 for the different validation datasets. The proposed RC model error depends on the fit obtained.…”
Section: Model Validation and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Although state estimation can reduce the short-term error [24,25] that appears due to not capturing the thermal interactions between boreholes, the RC network is not suitable for long-term predictions.…”
Section: Mpc In (Hybrid) Geothermal Systemsmentioning
confidence: 99%